CROSS-CULTURAL FEATURES OF INTERNATIONAL TOURISM - Квасова, Людмила; Бахорка, Марія (SWorldJournal, 2023)
The article deals with the problems of "cross-cultural shock" that arise in any international company. In particular, the work offers an analysis of cross-cultural differences of Western and Eastern cultures in comparison with Ukrainian national peculiari